PENGARUH VARIASI KECEPATAN PUTAR DAN DIAMETER PIN TOOLS TERHADAP KUAT GESER DAN STRUKTUR MAKRO SAMBUNGAN FRICTION STIR WELDING DISSIMILAR HIGH DENSITY POLYETHYLENE-POLYPROPYLENE - Suwanda, Totok; Ardiyansyah, Nur (Jurnal Rekayasa Mesin, 2023)
The purpose of this study is to find out the effect of pin tool turn speed and pin tool diameter on strong shear and macro structure on the friction stir welding dissimilar high-density polyethylene and polypropylene sheets. Variations in welding process parameters used in this study were: rotary speed of 980, 1560, 2360 rpm, and pin tool diameter of 4 and 5 mm. The shape of the cylinder pin, the feeding speed of 11 mm/min, and the plunge depth of 7.8 mm were maintained constant. The results showed that the highest shear strength value was obtained on the connection with a rotary speed of 1560 rpm and a pin tool diameter of 5 mm 4.8 N / mm2 or 23.71% of the tensile strength of raw material high density polyethylene. Observations of macro structures show that the pin tool diameter 5 mm has only slight defects in the stir zone.